SOSIALISASI MENGENAI MANFAAT MADU BAGI MURID SD NEGERI 1 KARANGANYAR - Gigih Kenanga Sari; Adi Norrochmat Pujiaharto; Hana Muizza; Iman Cahyani Putri; Syahrul Ramadhan (LPPM AN Nuur, 2024)
Background: There is not much information about the benefits of honey among consumers. Consumer knowledge regarding the benefits of honey needs to be increased to increase consumer knowledge. One effort that can be carried out is outreach activities regarding the benefits of honey. students at SD Negeri 1 Karanganyar are teenagers, so outreach activities regarding the benefits of honey are appropriate if given to students at SD Negeri 1 Karanganyar. Purpose: By conducting outreach activities to students at SD Negeri 1 Karanganyar, it is hoped that this can provide education about the benefits of honey for these students. Method: Socialization Regarding the benefits of honey, it is appropriate to give it to students at SD Negeri 1 Karanganyar. Results: There were 22 students in 1 class who understood the importance of drinking honey at SD Negeri 1 Karanganyar. Conclusion: Understanding of the presentation and students' awareness of the important benefits of drinking honey at SD Negeri 1 Karanganyar